903 Multidrug Resistant Clones of Ca-Mrsa Isolated from Chinese Children and the Resistance Determinants to Clindamycin and Mupirocin. (October 2012) - Shen, X; Wang, L
Abstract : This study aims to correlate the multidrug resistance (MDR) and ST clones of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA), to identify the genes responsible for clindamycin and mupirocin resistance in Staphylococcus aureus (SA) isolated from pediatric hospitals of Mainland China. Up to 435 SA isolates were collected. The findings indicated that in comparison with community-associated methicillin-susceptible S. aureus (CA-MSSA), the resistance rates of CA-MRSA to ciprofloxacin, chloramphenicol, gentamicin and tetracycline were higher. The resistance rates to clindamycin and erythromycin were highe (92.0% and 85.9%, respectively) in CA-MRSA. The MDR rates were 49.6%, 100% and 14% in CA-MRSA, HA-MRSA and CA-MSSA isolates, respectively. Five of seven ST(sequence typing) clones in CA-MRSA, namely ST59, ST338, ST45, ST910 and ST965, had MDR rates of more than 50% (67.9%, 87.5%, 100%, 50% and 83.3%, respectively). The constructive phenotype of macrolide-lincosamide-streptogramin B(MLSB) resistance (69%) and the ermB gene (38.1%) predominated among them. The resistant rate to mupirocin was 2.3%, and plasmids carrying the mupA gene varied in size between 23 and 54.2 kb in 6 strains with high-level resistance by Southern blot. The present study showed that the resistance to non-β-lactam antimicrobial agents, especially to clindamycin, was high in CA-MRSA isolated from Chinese children and the profile of resistance was related to clonal type.